2023
DOI: 10.3389/fnut.2023.1112028
|View full text |Cite
|
Sign up to set email alerts
|

There is a significantly inverse relationship between dietary riboflavin intake and prevalence of osteoporosis in women but not in men: Results from the TCLSIH cohort study

Abstract: BackgroundEpidemiological evidence for the relationship between riboflavin intake and bone health is inconsistent, and this relationship has not been examined in Chinese population. This study aimed to investigate the relationship between dietary intake of riboflavin and prevalence of osteoporosis in a Chinese adult population.MethodsA total of 5,607 participants (mean age, 61.2 years; males, 34.4%) were included in this cross-sectional study. We calculated the riboflavin intake by using the food frequency que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Zempleni et al reported that concentration of riboflavin in plasma was slightly lower during afternoon with less than 25% decrease in 9 healthy subjects (Zempleni et al, 1996). Finally, it is worth noting that there may be a gender difference in dietary riboflavin intake (Mataix et al, 2003, Wan et al, 2023. Further study is needed to evaluate the effect of a BCRP inhibitor on riboflavin levels in both male and female subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Zempleni et al reported that concentration of riboflavin in plasma was slightly lower during afternoon with less than 25% decrease in 9 healthy subjects (Zempleni et al, 1996). Finally, it is worth noting that there may be a gender difference in dietary riboflavin intake (Mataix et al, 2003, Wan et al, 2023. Further study is needed to evaluate the effect of a BCRP inhibitor on riboflavin levels in both male and female subjects.…”
Section: Discussionmentioning
confidence: 98%